The Legacy of Sebastian Kneipp: Linking Wellness, Naturopathic and Allopathic Medicine - Locher, Cornelia; Pforr, Christof (Mary Ann Liebert, Inc, 2014)
Sebastian Kneipp (1821–1897) is seen as a vital link between the European nature cure movement of the 19th century and American naturopathy. He promoted a holistic treatment concept founded on five pillars: hydroand phytotherapy, exercise, balanced nutrition, and regulative therapy. Kneipp attempted to bridge the gap with allopathic medicine, and many modern treatments that are based on his methods indeed blend wellness elements with naturopathic medicine and biomedicine. Because Kneipp’s approach to health and healing today are mainly covered in German literature, this paper aims to provide a broader international audience with insights into his life and his treatment methods and to highlight the profound influence Kneipp has had to this day on natural and preventive medicine. The paper emphasizes in particular the continued popularity of Kneipp’s holistic approach to health and well-being, which is evident in the many national and international Kneipp Associations, the globally operating Kneipp Werke, postgraduate qualifications in his treatment methods, and the existence of more than 60 accredited Kneipp spas and health resorts in Germany alone.